2022
DOI: 10.1177/00220345221087149
|View full text |Cite
|
Sign up to set email alerts
|

Microrobotics for Precision Biofilm Diagnostics and Treatment

Abstract: Advances in small-scale robotics and nanotechnology are providing previously unimagined opportunities for new diagnostic and therapeutic approaches with high precision, control, and efficiency. We designed microrobots for tetherless biofilm treatment and retrieval using iron oxide nanoparticles (NPs) with dual catalytic-magnetic functionality as building blocks. We show 2 distinct microrobotic platforms. The first system is formed from NPs that assemble into aggregated microswarms under magnetic fields that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…81 Moreover, this group also demonstrated that catalytic Fe 3 O 4 NPs assembled into microswarms or embedded in soft helicoids under magnetic fields can be controlled to disrupt and capture biofilms inside the root canal of teeth in an ex vivo model. 82…”
Section: Biofilm Colonized On Medical Cathetersmentioning
confidence: 99%
“…81 Moreover, this group also demonstrated that catalytic Fe 3 O 4 NPs assembled into microswarms or embedded in soft helicoids under magnetic fields can be controlled to disrupt and capture biofilms inside the root canal of teeth in an ex vivo model. 82…”
Section: Biofilm Colonized On Medical Cathetersmentioning
confidence: 99%
“…With respect to area of use , there are some area and disease that micro robots can be applied. Robotics in medicine encompasses targeted drug delivery [16], surgery assistance [17], and diagnostic support [18] across various fields are shown in Table 1.…”
Section: Urological Disordersmentioning
confidence: 99%
“…Our efforts are generating affordable and translatable approaches, including ultra-sensitive portable technologies for pathogen detection in saliva, Food and Drug Administration (FDA)–approved nanoparticles that target biofilms in severe caries, and high-precision microrobotics for biofilm disruption and lipid nanoparticle technologies for messenger RNA (mRNA) delivery (leveraged from the COVID-19 mRNA vaccine) to treat oral cancer ( Hwang et al 2019 ; Chen et al 2021 ; Liu et al 2021 ; Babeer et al 2022 ). Discoveries related to the microbiome and host immunity are revealing relationships among systemic diseases, suggesting new, personalized treatments and individualizing oral health care ( Teles et al 2021 ; Bostanci and Belibasakis 2023 ).…”
Section: Promoting Unique Collaborative Research and Supporting Trans...mentioning
confidence: 99%